Effects of Edible Algae Polysaccharides on Allergic, Inflammatory, and Anti-Tumor Responses Through Toll-Like Receptor 4 - Tominaga, Akira; Okuyama, Hiromi; Fukuoka, Satoshi; Taguchi, Takahiro; Kusumoto, Yutaka; Shimizu, Keiji; Ono, Shiro (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2010)
Algae are eaten as healthy foods in Asian countries. We summarize our recent results on the immunoregulatory role of polysaccharide fractions from edible algae on immediate hypersensitivity, delayed-type hypersensitivity, and antitumor immune responses. They are divided into two types. One is to manipulate immune response through toll-like receptor 4 (TLR 4). The other uses different receptors to modify the immune response. Petalonia binghamiae polysaccharide fraction and Spirulina pacifica complex polysaccharide attenuate the delayed-type hypersensitivity and tumor growth by reducing the production of inflammatory cytokine, IL-17 through TLR4. This is suggested from the results that these polysaccharide fractions could suppress the delayed-type hypersensitivity and tumor growth in C3H/HeN but not in tolllike receptor 4 mutant, C3H/HeJ mice. Alginic acid, the polysaccharide from brown algae suppressed tumor growth in both C3H/HeN and C3H/HeJ mice and did not suppress delayed-type hypersensitivity response significantly, when administered intraperitoneally. We propose the potential usefulness of edible algae as the fine tuning reagents of the immune response. We also summarize the recent advancement in the area of regulation of immune responses in relation to these polysaccharides.
Keywords: Algae